Prevalence and associated factors of cataract and cataract-related blindness in the Russian Ural Eye and Medical Study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Gilmanshin, Timur R.; Zainullin, Rinat M.; Nuriev, Ildar F.; Zaynetdinov, Artur F.; Israfilova, Gulnara Z.; Panda-Jonas, Songhomitra; Arslangareeva, Inga I.; Rakhimova, Ellina M.; Rusakova, Iulia A.; Jonas, Jost B. (Scientific reports, 2020)
Abstract - To assess the prevalence of cataract and cataract surgery in a population from Russia, we conducted the population-based Ural Eye and Medical Study with 5899 participants (80.5% out of 7328 eligible individuals), with an age of 40 + years as the eligibility criterion. In the phakic population, the prevalence of nuclear, cortical, subcapsular cataract and any cataract was 38.0% [95% confidence interval (CI) 36.6, 39.3], 14.5% (95% CI 13.5, 15.5), 0.6% (95% CI 0.4, 0.8) and 44.6% (95% CI 43.2, 46.0), respectively. A higher prevalence of nuclear cataract was associated with older age [odds ratio (OR) 1.10; 95% CI 1.10, 1.11], the female sex (OR 1.27; 95% CI 1.08, 1.50), urban region (OR 2.00; 95% CI 1.71, 2.33), a low educational level (OR 0.93; 95% CI 0.88, 0.98), a high diastolic blood pressure (OR 1.01; 95% CI 1.001, 1.02), a low serum concentration of high-density lipoproteins (OR 0.91; 95% CI 0.84, 0.98), more smoking package years (OR 1.01; 95% CI 1.01, 1.02), chronic kidney disease (OR 1.02; 95% CI 1.10, 1.03), a short axial length (OR 0.93; 95% CI 0.86, 0.99), and a low prevalence of age-related macular degeneration (OR 0.72; 95% CI 0.57, 0.92). The prevalence of previous cataract surgery conducted in 354/5885 individuals (6.0%; 95% CI 5.4, 6.6) increased from 0.4% (95% CI 0.0, 1.0) in the age group of 40-45 years to 37.6% (95% CI 30.9, 44.4) in the age group of 80 + years. Cataract was the cause of moderate-to-severe vision impairment in 109 (1.8%) individuals and of blindness in three (0.05%) individuals. The prevalence of cataract and cataract-related MSVI and blindness were relatively high; subsequently, the prevalence of previous cataract surgery was relatively low in this population from Russia.